2022
DOI: 10.3389/fpls.2022.942851
|View full text |Cite
|
Sign up to set email alerts
|

Canopy nitrogen addition enhance the photosynthetic rate of canopy species by improving leaf hydraulic conductivity in a subtropical forest

Abstract: Elucidating the effects of atmospheric nitrogen (N) deposition on the photosynthetic capacity of plants is critical to understand forest growth and conservation under global change. However, studies on this topic generally consider only understory N addition, which ignores the effect of canopy interception. In this study, we conducted a field experiment in a subtropical forest to compare the effects of canopy vs. understory N addition on the photosynthetic rate of canopy and understory species. We found that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Thus, it was understandable that the services of plant C sequestration in our study showed synergetic increases with the significant increase of plant N retention under the over-canopy N additions (Figures 2 and 6). Consistent with our result, another study at our study site found that over-canopy N additions significantly improve the photosynthetic rates of two dominant tree species, while understory N additions show no significant impacts (Wu et al, 2022).…”
Section: Synergetic Response Of Plant C N and P Retention To N Additionsupporting
confidence: 92%
“…Thus, it was understandable that the services of plant C sequestration in our study showed synergetic increases with the significant increase of plant N retention under the over-canopy N additions (Figures 2 and 6). Consistent with our result, another study at our study site found that over-canopy N additions significantly improve the photosynthetic rates of two dominant tree species, while understory N additions show no significant impacts (Wu et al, 2022).…”
Section: Synergetic Response Of Plant C N and P Retention To N Additionsupporting
confidence: 92%
“…These deposited gaseous and dissolved Nr are mainly intercepted by the canopy leaves and absorbed by ion exchange in the cuticle and/or simple diffusion in the stomata and enter the apoplast ( Rennenberg and Gessler, 1999 ; Sparks, 2009 ), which are then transported to the cells and assimilated and utilized by various enzyme systems such as nitrate reductase (NR), glutamine synthetase/glutamate synthase (GS/GOGAT) cycle in chloroplasts or plastids ( Krupa, 2003 ; Sparks, 2009 ). This process eventually leads to an increase in leaf N content and N metabolites, which in turn induces physiological responses and affects photosynthetic carbon assimilation capacity ( Castro et al., 2008 ; Mao et al., 2018 ; Hu et al., 2019 ; Wu et al., 2022 ), and also causes changes in leaf morphological and anatomical traits ( Zhu et al., 2020 ; Khan et al., 2020 ). Therefore, canopy leaves are also the first vegetative organ of plants to respond to dry and wet N deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that CN played a dual role in our study by reducing N leaching while increasing the annual mineralization rates in the spring, winter, and autumn, a finding that differs from the results of previous studies (Figure 3d,e). Previous research has linked CN with N leaching due to the N concentrations in tree organs, reflecting increased photosynthetic rates in forests [44,45].…”
Section: Seasonal Dynamics and The Impact Of Cn On N Processesmentioning
confidence: 99%